If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 4(x + -3) Reorder the terms: -5 + 6x = 4(x + -3) Reorder the terms: -5 + 6x = 4(-3 + x) -5 + 6x = (-3 * 4 + x * 4) -5 + 6x = (-12 + 4x) Solving -5 + 6x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 6x + -4x = -12 + 4x + -4x Combine like terms: 6x + -4x = 2x -5 + 2x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + 2x = -12 + 0 -5 + 2x = -12 Add '5' to each side of the equation. -5 + 5 + 2x = -12 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = -12 + 5 2x = -12 + 5 Combine like terms: -12 + 5 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5
| 3x^2y+12y=0 | | 4x+40-6x=3-9x+2 | | 8-2x=2x-4-7x | | 8-3x=3x-4-8x | | 67-6x=12x+21 | | 1+n=2 | | 8-8x=56-22x | | 13x=(33x-14) | | 2+9y-65x=345 | | 5a-7=3a-1 | | 82-6x=12x+22 | | 9-10x=169-45x | | (-3y-6z)(-9)= | | 43-6x=12x+19 | | 7-7x=107-42x | | 0.5b-10=24 | | 3(2x+5)=2(2-x) | | 8x-5=91 | | 0.6x^2+3.6x+3=0 | | m^3-6m^2+8m-7=0 | | m^4-6m^2+8m-7=0 | | 2+=a | | 7(2x-1)=x+3 | | 7(x-1)=x+3 | | -5=-5x | | 2x^4+x^3-3x^2+x+2=0 | | 9-3(x-1)=2x | | 4(2x-1)=x+3 | | X=2.5 | | -x^2-1+2m=0 | | 21-2x=5x-10.5 | | 4x+3+5x=6 |